Test Purpose Oriented I/O Conformance Test Selection with Colored Petri Nets - Jing Liu; Xinming Ye; Jiantao Zhou (Journal of Applied Mathematics)
This paper proposes an input-output conformance (IOCO) test selection method directed by test purpose model specified with colored Petri nets (CPN). Based on conformance testing oriented CPN models for specifying software functional behaviors and specific test purposes, respectively, feasible test cases are generated, guided by the CPN based IOCO relation, using synchronized model simulation with the proof of the soundness of test generation and the coverage towards test purposes. This test selection method integrates the merits the IOCO testing theory and the CPN modeling synergistically and is applied as a novel and applicable test selection method for actual testing practice of large-scale software systems. As the synchronized model simulation with two CPN models is irrespective of their model scale, the effectiveness and practicability of our test selection method are enhanced with scalability.